The effect of drought period on attack intensity of Empoasca sp and blister blight in Gambung tea plantation - Rezamela, Erdiansyah; Fauziah, Fani; Dalimoenthe, Salwa Lubnan (Jurnal Penelitian Teh dan Kina, 2016)
El-Nino had a significant impact on micro climate change including in rainfall, temperature and air humidity in Gambung Tea Plantation. In the dry season 2015, Gambung experienced four dry months that affect attack intensity of Empoasca and disease intensity of Blister Blight. This study aimed to determine the relationship between micro climate parameters and attack intensity of Empoasca and disease intensity of Blister Bright. Micro climate observation data were taken from Davis Automatic Weather Station (AWS) including rainfall intensity (mm), relative humidity (%) and maxium air temperature (0C). Attack intensity of Empoasca sp and Blister Bligh were observed by counting the number of healthy P+3 shoots as well as infected shoot from 200-500 gram of wet shoot sample randomly taken from container net at the plucking time. The results showed that the intensity of Empoasca decreased from 16.49% to 12.90% in the dry months from July to October 2015. The disease intensity of Blister Blight only occurred in July. There was a polynomial relationship among rainfall, temperature and humidity to the attack intensity of Empoasca with R2 values of 0.71, 0.77, 0.87, respectively the decrease of attack intensity occurred at ranfall intensity >140 mm, temperature >28Â°C and humidity >80%. Meanwhile linear relationship occurred among rainfall, temperature and humidity to the disease intensity of Blister Blight with R2 values of 0,98; 0,64; and 0,77, respectively the increasing of rainfall and humidity caused the increasing of disease intensity of Blister Blight. However disease intensity of Blister Blight decreased with increase in ambient temperature.